Long-term returns to local health-care spending - Jakub Cerveny; Jan C. van Ours (Tinbergen Institute, 2022)
This paper investigates the effects of health-care spending on mortality rates of heart attack patients. We relate in-hospital deaths to in-hospital end-of-life spending and post-discharge deaths to post-discharge health-care spending. In our analysis, we use detailed administrative data on individual personal characteristics and information about health-care expenses at the regional level. To account for potential selectivity in the region of health-care treatment we compare local patients with visitors and stayers with recent movers from a different region. In regions with higher health-care spending mortality after heart attacks is substantially lower. Apparently, there are long-term returns to local health-care spending.
Keywords: C41; H75; I11; I18; 330; Health-care spending; heart attack; mortality; duration models